2012
DOI: 10.3189/2012jog12j048
|View full text |Cite
|
Sign up to set email alerts
|

Subaqueous calving margin morphology at Mueller, Hooker and Tasman glaciers in Aoraki/Mount Cook National Park, New Zealand

Abstract: The subaqueous margins of calving glaciers have the potential to make significant contributions to glacier mass loss. However, to date, very little is known about the morphology and development of subaqueous margins. A unique combination of sub-bottom profile and bathymetric data collected between 2008 and 2010 in proglacial lakes at Mueller, Hooker and Tasman glaciers in New Zealand’s Southern Alps reveal subaqueous ice ramps extending up to 510 m from the terminus of each glacier. Ice ramp surfaces are undul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 36 publications
0
52
0
Order By: Relevance
“…The warmer water near the surface leads to higher melting rates in that region, resulting in submerged ice projecting beyond the subaerial face [Wright and Haynes, 1892;Savage, 2001;Stern et al, 2015]. Ice blocks have been found to surface 500 m from the terminus of LeConte Glacier in Alaska [Motyka, 1997], and submarine ice feet were recently observed to extend to similar distances at lake-terminating glaciers in New Zealand [Robertson et al, 2012]. Ice blocks have been found to surface 500 m from the terminus of LeConte Glacier in Alaska [Motyka, 1997], and submarine ice feet were recently observed to extend to similar distances at lake-terminating glaciers in New Zealand [Robertson et al, 2012].…”
Section: Introductionmentioning
confidence: 99%
“…The warmer water near the surface leads to higher melting rates in that region, resulting in submerged ice projecting beyond the subaerial face [Wright and Haynes, 1892;Savage, 2001;Stern et al, 2015]. Ice blocks have been found to surface 500 m from the terminus of LeConte Glacier in Alaska [Motyka, 1997], and submarine ice feet were recently observed to extend to similar distances at lake-terminating glaciers in New Zealand [Robertson et al, 2012]. Ice blocks have been found to surface 500 m from the terminus of LeConte Glacier in Alaska [Motyka, 1997], and submarine ice feet were recently observed to extend to similar distances at lake-terminating glaciers in New Zealand [Robertson et al, 2012].…”
Section: Introductionmentioning
confidence: 99%
“…Robertson et al (2012) found that ice ramps at the glacier end of glacial lakes tend to have slopes between 11 and 30 • and exhibit subaqueous calving. The level of knowledge of ice ramps in glacial lakes is limited, so it is difficult to determine ramp gradients exactly without detailed bathymetric information.…”
Section: Bathymetric Surveymentioning
confidence: 99%
“…The level of knowledge of ice ramps in glacial lakes is limited, so it is difficult to determine ramp gradients exactly without detailed bathymetric information. Rather than using the slopes from Robertson et al (2012), that are more applicable to the Tasman glacier area, the slopes have been changed to resemble the slopes measured at Imja Tsho in 1992 and 2002 by Sakai et al (2005). Figure 3 shows a longitudinal dashed line in the lake following the 1992 and 2002 transect from the western shoreline of the lake to the eastern shoreline reported by Sakai et al (2005).…”
Section: Bathymetric Surveymentioning
confidence: 99%
“…Bridge Lake, at 6.3 km 2 , is small relative to the much larger lakes of Southern Patagonia, while only marginally shallower. As such, many large Patagonian proglacial lakes contain vast areas that are free of the strong cooling influence of glacier runoff and trapped icebergs and can warm significantly, promoting thermal undercutting and enhancing further calving (Rohl, 2006;Rignot et al, 2010;Robertson et al, 2012).…”
Section: Locationmentioning
confidence: 99%